2023
DOI: 10.3390/antiox12061185
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Oral Antithrombotic Therapies in Atherosclerotic Disease and Atrial Fibrillation

Abstract: The thrombosis-related diseases are one of the leading causes of illness and death in the general population, and despite significant improvements in long-term survival due to remarkable advances in pharmacologic therapy, they continue to pose a tremendous burden on healthcare systems. The oxidative stress plays a role of pivotal importance in thrombosis pathophysiology. The anticoagulant and antiplatelet drugs commonly used in the management of thrombosis-related diseases show several pleiotropic effects, bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 202 publications
0
8
0
Order By: Relevance
“…However, whether this effect extends to compounds derived from RYR remains a matter of debate [ 66 ]. The inflammation plays a key role in the genesis of CVD [ 7 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] and cardiovascular drugs with pleiotropic anti-inflammatory effects showed a beneficial impact on cardiovascular mortality [ 7 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. The results of our study suggest that nutraceutical combination of leucoselect ® phytosome ® , red yeast rice, policosanol and folic acid is effective in term of LDL-C serum level reduction and shows an anti-inflammatory effect, reducing both the CPR and PLA2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether this effect extends to compounds derived from RYR remains a matter of debate [ 66 ]. The inflammation plays a key role in the genesis of CVD [ 7 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] and cardiovascular drugs with pleiotropic anti-inflammatory effects showed a beneficial impact on cardiovascular mortality [ 7 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. The results of our study suggest that nutraceutical combination of leucoselect ® phytosome ® , red yeast rice, policosanol and folic acid is effective in term of LDL-C serum level reduction and shows an anti-inflammatory effect, reducing both the CPR and PLA2.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases (CVDs) include several heterogeneous conditions mainly due to the atherosclerosis and are considered the leading cause of premature mortality and morbidity worldwide to date [ 1 , 2 , 3 ]. Atherosclerosis is a complex immuno-inflammatory process in which the low-density lipoprotein cholesterol (LDL-c) plays a role of pivotal importance in the genesis, progression and rupture of the lipid plaque; this latter condition may lead to thrombus formation, myocardial infarction and stroke [ 4 , 5 , 6 , 7 ]. The role of LDL-C as a causal factor in atherosclerosis is widely acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of precision medicine, the pleiotropic effects of anticoagulants are of significant interest and should be considered alongside drug–drug interactions and benefit/risk balance of drugs. Unfortunately, clinical data for direct anticancer effects are still lacking [ 125 , 126 ]. The “Thrombin Inhibition Preoperatively (TIP) in early breast cancer” is a clinical trial aiming to determine whether 14 days of a preoperative oral factor Xa inhibitor (rivaroxaban) in estrogen-receptor-negative early breast cancer patients results in inhibition of tumor proliferation determined by a reduction in tumor Ki67 from baseline (pre-treatment) to 14 days post treatment start (at the time of surgical excision).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, besides its antiplatelet activity, the treatment with ASA is associated with a significant reduction in cardiovascular events and a slowdown in the progression of atherosclerosis [40]. In addition, it has been reported that ASA exhibits radical scavenging and antioxidant properties [41][42][43][44]. In particular, ASA administration protects low-density lipoproteins from oxidative modifications [45], the vascular wall from oxygen radical damage [46], and prevents protein oxidation by acetylation of amino groups of lysine residues [47] or scavenging hydroxyl radicals [48].…”
Section: Discussionmentioning
confidence: 99%